Marketing to the 90s Generation Global Data on Society, Consumption, and Identity - Parment, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Marketing to the 90s Generation is based on original research conducted by sociologists and psychologists on generational cohorts, how they come about, what defines them and what it means to society, its institutions and companies.
Keywords: Marketing; International business enterprises; Market research; International economics; Marketing; International Business; Market Research/Competitive Intelligence; International Economics